The fall of the lower march/region of Al-Andalus in the hands of the spaniards - Mamduh Manoukh Dyab al-Naif,; Ahmad Hani al-Qatawneh, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study deals with one of the critical topics in our Arab-Islamic history, which is almost unknown to us because some of our historical Arabic sources and references have ignored it, namely the fall of Islamic Andalusia to the Spanish and Portuguese Christians. This negligence may be ascribed to our Arab historians’ focus on positive events highlighting the superiority and prosperity of Arabs and Muslims. In return, their oversight some of the adverse events that remained a stigma in Islamic history, and they only gave it scant attention without any elaboration. The study then addressed a stage of the fall of Andalusia, represented by the fall of the Lower Andalusian region and its base, the city of Badajoz, and then the rest of its district. To set the scene, the researcher deliberately talked first about the region’s geography and the importance of its cities. He then spoke about the Kingdom of Portugal, which endeavored to extend its territory at the expense of this region. Next, he discussed the status of this region during its occupation by Banu al-Aftas (a Berber Miknasa dynasty centered in Badajoz (1022–1094) in al-Andalus, Moorish Iberia), Almoravids (an imperial Berber Muslim dynasty) and Almohads (North African Berber Muslim), and the role of each of these governors in fighting the Christians and defending the region against their attacks.